A organização administrativa para a proteção do consumidor no Brasil - Louzada, Vanessa Vilarino (2015)
The work presented deals with the administrative organization given to the consumer. Therefore, it addresses the history of consumer relations, with the appearance of consumerist movement and evolution of consumer protection in the world, with some parts of the European Union and MERCOSUR, with a focus on Brazil. Following, we present an overview of public administration, through the relevant aspects of the CDC, National Policy for Consumer Relations, National Consumer Defense System, the exercise of police powers, regulatory agencies and conflicts of jurisdiction. Notes the administrative supervision by SENACON, DPDC, PROCONS and other agencies that make up the system are also part of the scrolling text. In the end, the work goes to new instruments as the improvement of the current system by PLANDEC, bills in progress on strengthening PROCONS and appearance of technology in managing and assisting agencies to provide a better service to consumers. You can check advances in the Brazilian consumerist harvest. However, the conclusion follows for necessary improvements in the SNDC, with a view to implementation of new guidelines for the standardization of administrative organization in the pursuit of effectiveness of existing conflicts in consumer relations, requiring the design of new legislation to regulate controversial issues existing today and give strength to the commands of state public policy for consumer protection. The purpose of the paper is to contribute to the debate on the subject, approach among the agencies that compose the SNDC, suggestions and measures in order to help the State to perform its task of providing the harmony of consumer relations, favoring even so reflex the judiciary, since of course the easy